Memory IgM protects endogenous insulin from autoimmune destruction. (9th August 2021) - Amendt, Timm; Jumaa, Hassan
Abstract: The enormous diversity of antibody specificities is generated by random rearrangement of immunoglobulin gene segments and is important for general protection against pathogens. Since random rearrangement harbors the risk of producing self‐destructive antibodies, it is assumed that autoreactive antibody specificities are removed during early B‐cell development leading to a peripheral compartment devoid of autoreactivity. Here, we immunized wild‐type mice with insulin as a common self‐antigen and monitored diabetes symptoms as a measure for autoimmune disease. Our results show that autoreactive anti‐insulin IgM and IgG antibodies associated with autoimmune diabetes can readily be generated in wild‐type animals. Surprisingly, recall immunizations induced increased titers of high‐affinity insulin‐specific IgM, which prevented autoimmune diabetes. We refer to this phenomenon as adaptive tolerance, in which high‐affinity memory IgM prevents autoimmune destruction by competing with self‐destructive antibodies. Together, this study suggests that B‐cell tolerance is not defined by the absolute elimination of autoreactive specificities, as harmful autoantibody responses can be generated in wild‐type animals. In contrast, inducible generation of autoantigen‐specific affinity‐matured IgM acts as a protective mechanism preventing self‐destruction. Synopsis: Autoantibodies that target self‐molecules are involved in autoimmune diseases. Here, a novel class of autoreactive IgM is found to be capable of protecting its cognate autoantigen from degradation. Antibody production depends on the antigen valency regardless of self or foreign . Soluble autoantigens are able to modulate autoantibody responses towards IgM. Affinity‐matured monospecific autoreactive IgM (PR‐IgM) protects its cognate autoantigen from degradation (adaptive tolerance). Abstract : Booster immunizations with a typical self‐antigen triggers a phenomenon called adaptive tolerance, in which high‐affinity memory IgM compete with self‐destructive antibodies thereby protecting autoantigens from degradation.